Cognitive profiles in persons with opioid use disorder enrolled in methadone treatment. Issue 4 (4th July 2022) - Sanborn, Victoria; Gunstad, John; Shrestha, Roman; Mistler, Colleen B.; Copenhaver, Michael M.
Abstract: Cognitive impairment is common in persons with opioid use disorder and associated with poor treatment outcomes, including elevated risk for relapse. Much less is known about the underlying structure of these deficits and the possible presence of cognitive phenotypes. A total of 177 adults (average 42.2 years of age, 52.0% male, 65.5% Caucasian) enrolled in a methadone maintenance treatment program completed the NIH Toolbox as part of a larger project. Cluster analyses revealed a 2-cluster solution–persons with intact cognitive function in all domains ( n  = 93; Intact) and those with impairments on tests of attention and executive function ( n  = 83; Impaired). Follow-up analyses revealed that the Impaired group was slightly older, more likely to self-identify as a racial/ethnic minority, and less likely to report consuming alcohol four or more times per week. These findings suggest the existence of distinct cognitive profiles in persons with opioid use disorder and encourage further examination, particularly studies to examine the possible benefits of routine screening for cognitive impairment as part of substance use treatment.